Wydawcy polskich edycji Potopu Henryka Sienkiewicza do 2002 roku - Foszczyńska, Beata (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2005)
[The Polish Publishers of Potop by Henryk Sienkiewicz until 2002] Novels by Henryk Sienkiewicz enjoy great popularity among readers. This fact is con-firmed by the rankings of the most popular writers and the most frequently read literary works, which are prepared from time to time. Sienkiewicz always occupies the top positions in them. That encourages publishing houses to publish his works willingly, especially the historic novels. Ever since 1884, when Potop was printed in the Warsaw “Słowo”, Krakow “Czas”, and “Kurier Poznański”, it has been published by the biggest publishing houses, such as Gebeth-ner and Wolff, or Ossolineum. After World War II, Potop was published by the State Publish-ing Institute. 54 editions of Potop were issued by that publisher. After 1989, political and economic changes took place in Poland which influenced the publishing market. Many new firms were created, such as Resovia, Euro, Beskidy Publishing House, Profit & Co., Arkadia, Univers, which willingly published the novel about the Swed-ish times. Foreign companies which could start to operate on the Polish market also published Sienkiewicz’s novels. The novel was published by Bertelsman Świat Książki, Philip Wilson. Potop found its place in the publishing repertoire of the firms specializing in publishing books for youth and children, educational books, and school reading matter: Siedmiogród, Podsied-lik-Raniowski i Spółka, Zielona Sowa, Kleks, Prószyński i S-ka, Greg. In recent years, Voca-tio, a company specializing in catholic books, has also publishd Potop. Publishing houses are very willing to publish Potop, especially the ones set on quick profit. It is related to the fact that it is school obligatory reading, so the demand for it has been and still is huge, especially in school libraries. Every bookstore has the Trilogy in its assort-ment as well. No home library could possibly do without this excellent work by Sienkiewicz